Adult Meaning Making in the Undergraduate Classroom - Carol E. Kasworm (Adult Education Research Conference, 1999)
This qualitative study explored adult student meaning making in an undergraduate classroom setting. Five key frames of meaning structures were delineated, suggesting highly complex and differing understandings of expert knowledge and adult learning engagement through classroom learning.